Morphology and kinematics of the gas envelope of the variable AGB star π1 Gruis*This paper makes use of the following ALMA data: ADS/JAO.ALMA# <2012.1.00524.S>. ALMA is a partnership of ESO (representing its member states), NSF (USA) and NINS (Japan), together with NRC (Canada) and NSC and ASIAA (Taiwan), and KASI (Republic of Korea) in cooperation with the Republic of Chile. The Joint ALMA Observatory is operated by ESO, AUI/NRAO and NAOJ. The data are retrieved from the JVO portal (http://jvo.nao.ac.jp/portal) operated by the NAOJ. (July 2016) - Nhung, Pham Tuyet; Hoai, Do Thi; Diep, Pham Ngoc; Phuong, Nguyen Thi; Thao, Nguyen Thi; Anh, Pham Tuan; Darriulat, Pierre
Abstract: Observations of the 12 CO(3–2) emission from the circumstellar envelope (CSE) of the variable star π 1 Gru using the compact array of the ALMA observatory have been recently made accessible to the public. An analysis of the morphology and kinematics of the CSE is presented with a result very similar to that obtained earlier for 12 CO(2–1) emission using the Submillimeter Array. A quantitative comparison is made using their flared disk model. A new model is presented that provides a significantly better description of the data, using radial winds and smooth evolutions of the radio emission and wind velocity from the stellar equator to the poles.